2017
DOI: 10.1080/08870446.2017.1325890
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking: Health impact, prevalence, correlates and interventions

Abstract: Background and objectives: Despite reductions in prevalence in recent years, tobacco smoking remains one of the main preventable causes of ill-health and premature death worldwide. This paper reviews the extent and nature of harms caused by smoking, the benefits of stopping, patterns of smoking, psychological, pharmacological and social factors that contribute to uptake and maintenance of smoking, the effectiveness of population and individual level interventions aimed at combatting tobacco smoking, and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
327
1
28

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 470 publications
(404 citation statements)
references
References 70 publications
7
327
1
28
Order By: Relevance
“…Rhodes et al (2017) found little evidence that mode of delivery moderated the effectiveness of physical activity interventions, although West (2017) noted that the chances of stopping smoking are highest when smokers use specialist face-toface behavioural support (along with either varenicline or nicotine replacement therapy). Online interventions are typically found to have small, but significant, effects on health behaviour (Webb et al, 2010), in line with many health behaviour interventions delivered via other modalities.…”
Section: Effectiveness Of Interventions To Change Health Behavioursmentioning
confidence: 99%
See 4 more Smart Citations
“…Rhodes et al (2017) found little evidence that mode of delivery moderated the effectiveness of physical activity interventions, although West (2017) noted that the chances of stopping smoking are highest when smokers use specialist face-toface behavioural support (along with either varenicline or nicotine replacement therapy). Online interventions are typically found to have small, but significant, effects on health behaviour (Webb et al, 2010), in line with many health behaviour interventions delivered via other modalities.…”
Section: Effectiveness Of Interventions To Change Health Behavioursmentioning
confidence: 99%
“…For example, as Kunstche et al (2017) note, increasing the price of alcohol (through minimum pricing legislation or increased taxation) is the most effective policy instrument to reduce alcohol consumption at a population level. West (2017) also highlight that increasing the cost of smoking is likely to lead to reduced levels of smoking given that for every 10% increase in the cost there is a corresponding 4% decrease in the number of cigarettes purchased. Considering changes to the physical environment, Kunstche et al (2017) highlight that there is some evidence that restricting alcohol sales on US college campuses, for example through reducing outlet density and hours of sales, can reduce student drinking.…”
Section: Effectiveness Of Interventions To Change Health Behavioursmentioning
confidence: 99%
See 3 more Smart Citations